The Crisis of Democratic Governance in Contemporary Indonesia - Marta, Auradian; Suwaryo, Utang; Sulaeman, Affan; Agustino, Leo (Jurnal Ilmiah Peuradeun, 2020)
This article attempts to discuss the practice of democratic governance in contemporary Indonesia. This study is essential since Indonesia is one of the countries transitioning from authoritarianism towards democracy following the fall of Suharto’s regime. This study shall answer whether democratic governance in Indonesia experiences a crisis, with a focus of analysis on the four dimensions of democratic governance, namely: (1) rule of law, (2) human rights, (3) civil society, and (4) elections and political process. This study applies a qualitative method by collecting data from document studies and literary studies. The findings in this study indicate that democratic governance in Indonesia experiences a crisis as evidenced by the remaining-weak legal supremacy in Indonesia, and the existence of violations of the implementation of human rights, eventually led to horizontal conflicts. The inability of civil society organizations to carry out their functions in democratization as an intermediary between the community and the state as well as to influence government policies for the public interest. Another recent weakness is there are still strong issues related to primordialism in the occasion of General Elections. This crisis of democratic governance shall bring Indonesia to "the decline of democracy" instead of democratic consolidation.